(untitled) (Global Journal of Human-Social Science, 2020)
Introduction-Bangladesh has been the host state of a large number of Rohingya refugees since August 2017. Rohingya, An ethnic minority group of Rakhine state, Myanmar, have been fleeing to Bangladesh after the Myanmar army started an ethnic cleansing on that area in august 2017. Since then, Bangladesh has been hosting around 1.1 million Rohingya refugees till now. In the first three months of the crisis, the majority arrived. During the first half of 2018, an estimated 12,000 people entered Bangladesh. Women and children are the vast majority in Bangladesh, and more than 40 percent are under 12 years of age (UNHCR 2020). As per the latest update of UNHCR, 860,243 Rohingya refugees are living in 187,534 households inside the camps (UNHCR 2020). After three years of this influx, Bangladesh is bearing the burden of Rohingya refugees and repatriation from Bangladesh is a far cry from reality. As (Mallick 2020) explain that, due to China and India’s rising economic and strategic interests in repatriating the Rohingya refugees to the Rakhine State, Myanmar, foreign and regional organizations were unable to take any visible action. Organizations such as the United Nations, OIC, ASEAN, and other regional bodies have struggled to put pressure on Myanmar to take back Bangladeshi Rohingya refugees.